Alexithymia and Autistic Traits: Associations With Social and Emotional Challenges Among College Students - Vaiouli, Potheini; Panayiotou, Georgia (Frontiers in Neuroscience, 2021)
Background. Alexithymia is a multifaceted personality construct defined by marked difficulties in identifying and describing feelings and in externally oriented thinking. Given its intrinsic role in social-emotional processing, alexithymia is now recognized as a trans-diagnostic trait in a range of neurodevelopmental disorders, including autism. Research has pinpointed to the co-occurrence of autism with characteristics typical of alexithymic normative samples, such as social-communication difficulties and decreased emotion regulation abilities. Nonetheless, the role of individual facets of alexithymia in predicting challenges in social communication functioning is still understudied. Methods. In total, 275 young adults completed the Toronto Alexithymia Scale, the Autism Spectrum Quotient (short form), the Interpersonal Competence Questionnaire, and the Difficulties in Emotion Regulation Scale self-reported questionnaires for assessing alexithymic and autistic traits, social-communication abilities, and emotion regulation difficulties. We used regression models to establish cross-sectional associations between autism, alexithymia, and social-emotional difficulties. Also, we ran a parallel mediation analysis to determine whether the relationship between autistic traits and emotion regulations challenges are mediated by Alexithymia facets. Results. Analysis showed a significant positive association between autistic traits and alexithymic traits and between autistic traits and emotion regulation difficulties while, as expected, autistic traits were negatively correlated with social skills. A significant relationship was found among the participants’ levels of alexithymia and their interpersonal skills with two of three alexithymic subscales significantly contributing to the model. Similarly, a significant relationship was found among alexithymia subscales and emotion regulation difficulties with all three alexithymia subscales being statistically significant. Finally, analysis on two mediator models indicated a significant effect of autistic traits on social skills mediated by alexithymic traits as well as a significant indirect effect of autistic traits on emotion regulation difficulties mediated by alexithymic traits. Conclusions. The results of this study provide evidence of the influence of different alexithymic facets on the relationship between autistic traits and social-emotional challenges in young adults. Longitudinal studies may explore further alexithymia and its associations with social-emotional difficulties in autism as well as the potential implications of these findings in intervention and treatment programs.